2005
DOI: 10.1124/mol.104.006437
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes of GABA Synaptic Transient in Cerebellar Granule Cells

Abstract: The time course of synaptic currents is largely determined by the microscopic gating of the postsynaptic receptors and the temporal profile of the synaptic neurotransmitter concentration. Although several lines of evidence indicate that developmental changes of GABAergic synaptic current time course are clearly correlated with a switch in postsynaptic receptors, much less is known about the modification of GABA release during development. To address this issue, we studied the sensitivity of miniature inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…We found that TPMPA similarly inhibited mIPSCs in control GFP and NLG-2 over-expressing CGCs both at DIV7-8 and DIV12-14 cultures (Fig 5). However, consistent with previous work (47), we did observe the differential inhibition of mIPSCs between young (DIV7-8) and old (DIV12-14) cultures (Fig 5A, B), suggesting a stronger presynaptic GABA release in young neurons. Together, these results may suggest that NLG-2 does not alter uniquantal GABA release, and the fast decay of mIPSC induced by NLG-2 was due to the differential expression of postsynaptic GABA A receptor subtypes.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found that TPMPA similarly inhibited mIPSCs in control GFP and NLG-2 over-expressing CGCs both at DIV7-8 and DIV12-14 cultures (Fig 5). However, consistent with previous work (47), we did observe the differential inhibition of mIPSCs between young (DIV7-8) and old (DIV12-14) cultures (Fig 5A, B), suggesting a stronger presynaptic GABA release in young neurons. Together, these results may suggest that NLG-2 does not alter uniquantal GABA release, and the fast decay of mIPSC induced by NLG-2 was due to the differential expression of postsynaptic GABA A receptor subtypes.…”
Section: Resultssupporting
confidence: 93%
“…Of note, a prerequisite for an efficient displacement of competitive antagonist by synaptic agonist is that the dissociation time constant of the antagonist is comparable with the duration time of the GABA transient in synaptic cleft. TPMPA was found to be a suitable tool to reveal differences in the GABA transient in synaptic cleft due to its fast dissociation time constant of ~0.46ms (45-47). In this set of studies, GABAergic mIPSCs were recorded in absence and presence of TPMPA at two different culture ages, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For these experiments we examined the effect of TPMPA, a low-affinity competitive GABA A receptor antagonist. The block of postsynaptic GABA A receptor-mediated responses is dependent upon GABA concentration at the synapse (Barberis et al, 2005; Szabadics et al, 2007). When synaptic GABA levels are low, TPMPA is displaced from postsynaptic receptors to a lesser extent, and thus IPSCs are more effectively blocked.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the decay time constants of remaining receptors are prolonged, reflecting the substitution of a1-GABA A receptors by another subtype. Since a1-GABA A receptors have faster kinetics than those containing the a2 or a3 subunits (88,89), this factor was taken as an index for the sustained presence of these subunits in mature granule cells of mutant mice (87,90).…”
Section: Effects Of Targeted Subunit Gene Deletion On Cerebellar Gabamentioning
confidence: 99%